2011
DOI: 10.2174/187231211796904991
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Anti-Tumor Activity of Uncommon In Vitro and In Vivo Metabolites of CPI-613, a Novel Anti-Tumor Compound That Selectively Alters Tumor Energy Metabolism

Abstract: CPI-613 is a novel anti-tumor compound with a mechanism-of-action which appears distinct from the current classes of anti-cancer agents used in the clinic. CPI-613 demonstrates both in vitro and in vivo anti-tumor activity. In vitro metabolic studies using liver S9 were performed which demonstrated that CPI-613 undergoes both phase 1 (oxidation) and phase 2 (glucuronidation) transformations. Its metabolic half-life varied between species and ranged from 8 minutes (Hanford minipig) to 47 minutes (CD-1 mouse). W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Previous CPI studies have focused on investigating the efficacy of this drug in anti-cancer treatment as a tumor-specific antimitochondrial mediator that has been tested in a number of cancerous cell lines as well as in vivo (Lee et al, 2011a , 2011b ; 2014 ; Pardee et al, 2014 ; Perera et al, 2012 ; Senzer et al, 2012 ; Zachar et al, 2011 ). A comparison of CPI treatment between cancerous and non-cancerous cell lines from lung, breast, and kidney demonstrated that CPI reduced cell survival in all of the cancerous lines compared to the non-cancerous lines, implying non-cancerous cells are less sensitive to CPI (Zachar et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous CPI studies have focused on investigating the efficacy of this drug in anti-cancer treatment as a tumor-specific antimitochondrial mediator that has been tested in a number of cancerous cell lines as well as in vivo (Lee et al, 2011a , 2011b ; 2014 ; Pardee et al, 2014 ; Perera et al, 2012 ; Senzer et al, 2012 ; Zachar et al, 2011 ). A comparison of CPI treatment between cancerous and non-cancerous cell lines from lung, breast, and kidney demonstrated that CPI reduced cell survival in all of the cancerous lines compared to the non-cancerous lines, implying non-cancerous cells are less sensitive to CPI (Zachar et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…By comparing to non-transformed cell lines, CPI-613 displays tumor selectivity. Additionally, treatment with CPI-613 leads to cell death also in p53-deficient or KRAS -mutated cell lines [ 194 , 212 , 213 ] as well as in drug-resistant cells [ 214 , 215 , 216 ]. Microarray data showed the reduced expression levels of cyclins as well as CDK2 , p27 and p19 , which point to a preceding cell cycle arrest [ 217 , 218 ].…”
Section: The Lipoic Acid Derivative Cpi-613 In Cancer Therapymentioning
confidence: 99%
“…Once administered, CPI-613 undergoes biotransformation including phase I oxidation via CYP3A4/5 and CYP2C8 with partially coupled phase II O -glucuronidation and sulfoxide formation as shown in vitro using human S9 mix [ 214 , 215 ]. With respect to cytotoxicity, drug metabolism leads to a decrease or loss of cytotoxicity as compared to the parent compound.…”
Section: The Lipoic Acid Derivative Cpi-613 In Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of action of CPI-613 appears distinct from that of the standard classes of anticancer agents used in the clinic, it clearly demonstrates both in vitro and in vivo anticancer activity [ 8 ]. The anticancer effect of CPI-613 has been evaluated in xenograft models of pancreatic cancer [ 9 ] and applied in patients with metastatic pancreatic cancer, where it has shown strong tumor growth inhibition at its maximum tolerated dose of 500 mg/m 2 [ 10 ].…”
Section: Introductionmentioning
confidence: 99%